Assessing the Effect of Tax Administration on Smes Tax Compliance Level in Kogi State - Onoja, Emmanuel Eneche; Odoma, Ademu Usman (European Journal of Economics and Business Studies, 2021)
Effective tax administration is important for tax revenue generation. It has been observed that the loss of revenue caused by widespread of tax evasion and tax avoidance in Nigeria is due to inefficient and inept tax administration. The most common problem faced by taxpayers is to understand the instructions in the tax pack. This study assesses the burden of tax administration on taxpayers’ compliance level in Kogi State. The population of this study comprises of registered small scale businesses taxpayers in Kogi State, with a sample size of three hundred and seventy eight (378). Questionnaire was used to generate the data while One Sample chi-square test was used to test the null hypotheses. The result shows that administrative tax compliance costs have a significant effect on tax compliance level in Kogi State. The study recommends that the tax authority should make tax administration less complex in the area of tax procedures, tax rules and tax computation to enhance the level of tax payment in the State.